Towards a three-dimensional framework of centrally regulated and goal-directed exercise behaviour: a narrative review. Issue 15 (23rd August 2017) - Venhorst, Andreas; Micklewright, Dominic; Noakes, Timothy D
Abstract : The Central Governor Model (CGM) ignited a paradigm shift from concepts of catastrophic failure towards central regulation of exercise performance. However, the CGM has focused on the central integration of afferent feedback in homeostatic control. Accordingly, it neglected the important role of volitional self-regulatory control and the integration of affective components inherently attached to all physiological cues. Another limitation is the large reliance on the Gestalt phenomenon of perceived exertion. Thus, progress towards a comprehensive multidimensional model of perceived fatigability and exercise regulation is needed. Drawing on Gate Control Theory of pain, we propose a three-dimensional framework of centrally regulated and goal-directed exercise behaviour, which differentiates between sensory, affective and cognitive processes shaping the perceptual milieu during exercise. We propose that: (A) perceived mental strain and perceived physical strain are primary determinants of pacing behaviour reflecting sensory-discriminatory processes necessary to align planned behaviour with current physiological state, (B) core affect plays a primary and mediatory role in exercise and performance regulation, and its underlying two dimensions hedonicity and arousal reflect affective-motivational processes triggering approach and avoidance behaviour, and (C) the mindset-shift associated with an action crisis plays a primary role in volitional self-regulatory control reflecting cognitive-evaluative processes between further goal-pursuit and goal-disengagement. The proposed framework has the potential to enrich theory development in centrally regulated and goal-directed exercise behaviour by emphasising the multidimensional dynamic processes underpinning perceived fatigability and provides a practical outline for investigating the complex interplay between the psychophysiological determinants of pacing and performance during prolonged endurance exercise.